Sodium‐glucose cotransporter‐2 inhibitors in heart failure: an updated meta‐analysis - Yang Cao; Pengxiao Li; Yi Li; Yaling Han (ESC Heart Failure)
Abstract Aims We aimed to examine efficacy and safety outcomes of sodium‐glucose cotransporter‐2 inhibitor (SGLT2i) for the treatment of heart failure (HF), especially in patients with heart failure with preserved ejection fraction (HFpEF). Methods and results PubMed, Web of Science, and Cochrane Library were searched to identify randomized controlled trials comparing SGLT2i vs. placebo in HF patients. A total of 10 studies with 23 852 HF patients were eventually included. Compared with placebo, SGLT2i is associated with a lower incidence of composite of first hospitalization for heart failure (HHF) or cardiovascular death (CV death) [hazard ratio (HR) = 0.76 95% confidence interval (CI) = 0.71–0.81], which is consistent regardless of the diabetes status, type of gliflozines used, and follow‐up duration. SGLT2i can reduce the risk of total HHF or CV death (HR = 0.74, 95%CI = 0.68–0.81), first HHF (HR = 0.69, 95%CI = 0.64–0.75), CV death (HR = 0.88, 95%CI = 0.80–0.96), any death (HR = 0.90, 95%CI = 0.83–0.97), and any serious events (HR = 0.90, 95%CI = 0.87–0.93) in HF patients, at the cost of increased risk of urinary tract infections (risk ratio = 1.17, 95%CI = 1.03–1.33). In HFpEF patients, SGLT2i is associated with a significant reduction of composite of first HHF or CV death (HR = 0.81, 95%CI = 0.73–0.91), first HHF (HR = 0.71, 95%CI = 0.62–0.82), and total HHF or CV death (HR = 0.61, 95%CI = 0.43–0.86). Conclusions Sodium‐glucose cotransporter‐2 inhibitor contributed to better efficacy outcomes in overall HF patients and showed an inspiring breakthrough in the treatment of HFpEF.